The Harbinger transposon‐derived gene PANDA epigenetically coordinates panicle number and grain size in rice. Issue 6 (16th March 2022) - Mao, Donghai; Tao, Shentong; Li, Xin; Gao, Dongying; Tang, Mingfeng; Liu, Chengbing; Wu, Dan; Bai, Liangli; He, Zhankun; Wang, Xiaodong; Yang, Lei; Zhu, Yuxing; et al.
Summary: Transposons significantly contribute to genome fractions in many plants. Although numerous transposon‐related mutations have been identified, the evidence regarding transposon‐derived genes regulating crop yield and other agronomic traits is very limited. In this study, we characterized a rice Harbinger transposon‐derived gene called PANICLE NUMBER AND GRAIN SIZE ( PANDA ), which epigenetically coordinates panicle number and grain size. Mutation of PANDA caused reduced panicle number but increased grain size in rice, while transgenic plants overexpressing this gene showed the opposite phenotypic change. The PANDA ‐encoding protein can bind to the core polycomb repressive complex 2 (PRC2) components OsMSI1 and OsFIE2, and regulates the deposition of H3K27me3 in the target genes, thereby epigenetically repressing their expression. Among the target genes, both OsMADS55 and OsEMF1 were negative regulators of panicle number but positive regulators of grain size, partly explaining the involvement of PANDA in balancing panicle number and grain size. Moreover, moderate overexpression of PANDA driven by its own promoter in the indica rice cultivar can increase grain yield. Thus, our findings present a novel insight into the epigenetic control of rice yield traits by a Harbinger transposon‐derived gene and provide its potential application for rice yield improvement.